Earliest direct evidence of bronze age betel nut use: biomolecular analysis of dental calculus from Nong Ratchawat, Thailand - Moonkham, Piyawit; Tushingham, Shannon; Zimmermann, Mario; Brownstein, Korey J.; Devanwaropakorn, Charmsirin; Duangsakul, Suphamas; Gang, David R. (Frontiers in Environmental Archaeology, 2025)
IntroductionThe social and temporal dimensions of psychoactive plant use in prehistoric Southeast Asia remain elusive.MethodHere, we employ novel biomolecular methods to provide direct evidence of betel nut chewing in ancient dental calculus from Nong Ratchawat, Central Thailand. Method validation confirmed reliable detection of key compounds through LC-MS analysis of experimental control samples.ResultSubsequent analysis of 36 archaeological samples from six ~4,000-year-old burials revealed diagnostic arecoline derivatives in a single female burial, representing the earliest such evidence in Southeast Asia.DiscussionThis identification, despite the lack of traditional archaeological indicators, demonstrates the power of dental calculus analysis to illuminate prehistoric psychoactive substance use. This study establishes the antiquity of betel nut consumption in mid-Holocene Thailand and provides new methodological avenues for future research in Southeast Asia.